VD_FINDINFO ML / 2010 / 179 vom 18. März 2010 - VD Tribunal cantonal (2010)
COTISATION AVS/AI/APG, DÉCISION DE COTISATIONS, MAINLEVÉE DÉFINITIVE | 97 LAVS, 80 LP, 52 LPGA, 54 LPGA, 34a RAVS, 81 al. 1 RAVS